Perancangan Database Sistem Informasi Akuntansi Untuk Perusahaan Skala Kecil dan Menengah Berbasis Service Oriented Architecture Dengan Implementasi Menggunakan Cloud Computing - Software As A Service (SaaS) - Nuraminah, Ahlijati (I-STATEMENT: Information System and Technology Management, 2017)
One of the developments in information technology that able to yield a positive impact to business continuity is cloud computing technology. That characteristics of cloud computing can be used for the development of information systems that generally used by small and medium scale enterprises. To be able to develop such a system, it is necessary to design appropriate data and architecture in order to meet the characteristics of cloud computing services, especially software as a service (SaaS). The design of data is also expected to adopt the concept of Service Oriented Architecture (SOA) in order to design a data model that can be used more flexibly. The results obtained are in the form of a design of the system architecture and data modeling database. The database model is divided into two main databases: accounting database and financial database. The design result was met the rules of service oriented architecture and multitenancy of cloud computing software as a service.